BUILDING HARMONY: THE ROLE OF BUDDHISTS IN REALIZING INTERFAITH TOLERANCE - Suryanto, Eko; Kabri, Kabri; Fendy, Fendy (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2024)
This article examines the strengthening of Buddhist community through religious tolerance in Indonesia, amid increasing cases of intolerance which recorded 217 events with 329 violations of religious freedom in 2023. This study aims to analyze various aspects of Buddhist community strengthening, including attitudes towards traditional beliefs, religious attitude phenomena, sectarian and non-sectarian analysis, plurality and multiculturalism, inclusivism and exclusivism, as well as religious tolerance based on Upali Sutta, Kalama Sutta, and King Asoka's policies. Using library research methods with content analysis techniques, this study examines various related literature sources. The results show that strengthening the Buddhist community can be achieved through pluralistic engagement, cultural integration, reduction of violent attitudes, non-sectarian perspectives, and the application of inclusive values in modern contexts. The study concludes that the Buddhist approach to religious tolerance, rooted in the principles of pluralistic engagement and cultural integration, provides a strong foundation for building social harmony and reducing inter-religious conflicts in Indonesia.